2014
DOI: 10.1038/onc.2014.32
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Epstein–Barr virus oncoprotein LMP1-mediated glycolysis sensitizes nasopharyngeal carcinoma to radiation therapy

Abstract: Our goal in this work was to illustrate the Epstein-Barr virus (EBV)-modulated global biochemical profile and provide a novel metabolism-related target to improve the therapeutic regimen of nasopharyngeal carcinoma (NPC). We used a metabolomics approach to investigate EBV-modulated metabolic changes, and found that the exogenous overexpression of the EBV-encoded latent membrane protein 1 (LMP1) significantly increased glycolysis. The deregulation of several glycolytic genes, including hexokinase 2 (HK2), was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
170
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(181 citation statements)
references
References 44 publications
10
170
0
1
Order By: Relevance
“…One of the important functions for mTORC1 is regulation of energy metabolism in cancer cells. Recent studies have shown that LMP1 promotes aerobic glycolysis in NPC cells (25,26). Aerobic glycolysis is closely correlated with a higher rate of glucose uptake, which is regulated by glucose transporters (Gluts).…”
Section: Resultsmentioning
confidence: 99%
“…One of the important functions for mTORC1 is regulation of energy metabolism in cancer cells. Recent studies have shown that LMP1 promotes aerobic glycolysis in NPC cells (25,26). Aerobic glycolysis is closely correlated with a higher rate of glucose uptake, which is regulated by glucose transporters (Gluts).…”
Section: Resultsmentioning
confidence: 99%
“…The CNE1-LMP1 cell line, which stably expresses LMP1, was obtained from the Cancer Research Institute of Central South University (26,29). All these cells were also preserved at the Cancer Research Insitute at Xiangya School of Medicine (26,27,29,30 (30). CNE1 cells (5x10 5 cells/well) were transfected with different concentrations of pSG5-LMP1 plasmid (0, 0.5 and 1 µg/well) or with control pSG5 vector (Agilent Technologies, Inc., Santa Clara, CA, USA; 1 µg/well) using Lipofectamine 2000 (Invitrogen; Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…LMP1 is sufficient to induce aerobic glycolysis in NPC cells (60), and GLUT1 depletion suppresses nasopharyngeal epithelial cell aerobic glycolysis, proliferation, and colony formation (62). Further studies are required to determine whether additional EBV latency proteins contribute to this phenotype.…”
Section: Lmp1 Promotes Aerobic Glycolysismentioning
confidence: 99%